Systematizing peer recovery support services for substance use disorder: a taxonomy for measuring recovery milestones - Horn, Kimberly; Flinn, Ryan E.; Hagaman, Angela Marie; Zajac, Kristyn; Hoffman, Lauren A.; Poulsen, Melissa N.; Cioffi, Camille C.; Jean-Berluche, Ducel; Spana, Ethan; Hibbard, Patrick F.; Drazdowski, Tess K.; Hogue, Aaron (Frontiers in Public Health, 2025)
BackgroundRecovery from substance use disorder (SUD) is a complex and individualized process requiring multifaceted support systems. Peer recovery support services (PRSS), provided by Peer Workers, bridge the gap between formal intervention and personal recovery experiences. Drawing on shared lived experience, Peer Workers offer essential support to fellow Peers navigating recovery. However, variability in PRSS roles, training, and settings creates challenges for consistent evaluation and measurement of effectiveness.ObjectiveIntroduce a systematic taxonomy to clarify the roles, functions, and activities within PRSS, providing a structured framework for evaluating their impact on key SUD recovery milestones.MethodsThe taxonomy was developed through a rapid narrative literature review, expert consultation, and an iterative consensus process informed by a Delphi-like approach. A multidisciplinary task group of PRSS scientists and practitioners, SUD treatment providers, and individuals in recovery contributed to its refinement. The framework aligns with key components from SAMHSA’s national standards (SAMHSA, 2023) to enhance consistency across practice settings.ResultsComprising six primary taxons and 20 branches, the taxonomy organizes PRSS components into structured categories. It classifies variations in lived experience (e.g., direct, indirect, and hybrid), training levels (e.g., basic, specialized, continuous education, and formal education), support approaches (e.g., Peer Worker-led services), and support settings (e.g., community-based, clinical, and justice system). Additionally, it categorizes peer support activities into four core domains: emotional, informational, instrumental, and affiliational support. The taxonomy integrates a structured model for PRSS evaluation, identifying mediators (e.g., support approaches) and moderators (e.g., training levels) that influence recovery outcomes.ConclusionThe proposed taxonomy and integrated evaluation model provide a standardized framework for researchers and practitioners to systematically assess PRSS impact on recovery milestones. By establishing a common language, the taxonomy enhances consistency in PRSS research, identifies empirically supported peer support practices, and informs targeted training and strategic implementation. Future research should prioritize empirical testing of this framework to refine its applicability across diverse PRSS settings and enhance intervention effectiveness and scalability.